Correction: Preclinical appraisal of terbutaline analogues in precipitation of autism spectrum disorder. Issue 127 (11th December 2015) - Sharma, Neha; Gautam, Swetlana; Devi, Uma; Singh, Manjari; Rawat, Jitendra K.; Sethi, Nikunj; Saraf, Shubhini A.; Kaithwas, Gaurav
Abstract : Correction for 'Preclinical appraisal of terbutaline analogues in precipitation of autism spectrum disorder' by Neha Sharma et al., RSC Adv., 2015, 5, 39003–39011.